2020
DOI: 10.1038/s41551-020-00619-3
|View full text |Cite
|
Sign up to set email alerts
|

Design and clinical implementation of an open-source bionic leg

Abstract: In individuals with lower-limb amputations, robotic prostheses can increase walking speed, and reduce energy use, the incidence of falls and the development of secondary complications. However, safe and reliable prosthetic-limb control strategies for robust ambulation in real-world settings remain out of reach, partly because control strategies have been tested with different robotic hardware in constrained laboratory settings. Here, we report the design and clinical implementation of an integrated robotic kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(97 citation statements)
references
References 61 publications
1
87
0
Order By: Relevance
“…Because it is quite difficult to control one’s own EEG signals, training protocols need to provide visual feedback that allows the subjects to monitor their progress [ 179 ]. VR can provide such feedback for tracking the progress of a BCI-controlling task [ 180 ] and can even sustain the illusion of embodiment through suitable sensory stimulation to reward specific brain-activity patterns [ 181 , 182 , 183 , 184 , 185 , 186 ]. Indeed, transcranial magnetic stimulation (TMS) has been successfully applied to achieve a sense of ownership and a sense of agency over an avatar in immersive VR [ 187 ].…”
Section: Virtual Reality For Replacement Of Functionmentioning
confidence: 99%
“…Because it is quite difficult to control one’s own EEG signals, training protocols need to provide visual feedback that allows the subjects to monitor their progress [ 179 ]. VR can provide such feedback for tracking the progress of a BCI-controlling task [ 180 ] and can even sustain the illusion of embodiment through suitable sensory stimulation to reward specific brain-activity patterns [ 181 , 182 , 183 , 184 , 185 , 186 ]. Indeed, transcranial magnetic stimulation (TMS) has been successfully applied to achieve a sense of ownership and a sense of agency over an avatar in immersive VR [ 187 ].…”
Section: Virtual Reality For Replacement Of Functionmentioning
confidence: 99%
“…Prosthetics of the knee joint with impedance control have been developed by Biomechatronics Group, Massachusetts Institute of Technology, and Delft University of Technology [190]. Other commercial examples of bionic ankles are: the MIT Powered Ankle, the first commercialized powered ankle prosthesis by Ottobock and previously by BionX; the one from Arizona State University, commercialized by SpringActive; one from the Mechanics Research Group (Vrije Universiteit Brussel), commercialized by Axiles Bionics; and one from the Biomechatronics Lab (Stanford University), commercialized by Humotech [191]. Several 3D printed LL prosthetic designs are being fabricated by companies, such as the bionic leg prostheses by BionX Medical Technologies, the Exo-Prosthetic leg, and the Andiamo leg [192].…”
Section: Examples Of Neuroprostheticsmentioning
confidence: 99%
“…Active or powered prostheses are actuated by motors and provide greater performance and functionality. Various research groups are developing powered knee, ankle, or leg prostheses that provide kinematics that are similar to able-bodied movement in a more effective way than passive and semi-active systems [ 191 ]. LL prosthetics that control both knee and ankle joints are the Vanderbilt Prosthetic Leg by Center for Intelligent Mechatronics, the OSL by Neurobionics Lab, and the AMPRO by Advanced Mechanical Bipedal Experimental Robotics Lab [ 191 ].…”
Section: Technological Synergies Driving Neural Rehabilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to morbidity, a US-Army study showed only a 2.3% return-toduty rate for soldiers who had sustained a traumatic amputation (of whom most had suffered only partial hand or foot loss) (Kishbaugh et al, 1995). The 2013 Boston Marathon bombing caused 17 lower limb traumatic amputations and a further 10 severe soft tissue extremity injuries (King et al, 2015); the morbidity in these civilian injuries is likewise extensive with reduced mobility, phantom limb pain, and an overall reduced quality of life reported (Sinha et al, 2011;Azocar et al, 2020). To limit future morbidity and mortality through mitigative strategies, an accurate understanding of the mechanism of injury is essential.…”
Section: Introductionmentioning
confidence: 99%